The Effect of Changes in Perception of Time on Demographic Processes - Antal, Antal z. (European Journal of Mental Health, 2008)
The paper first analyses the new changes of demographic processes that have taken place in the past decades, next a point of consideration, namely changes in the perception of time, is presented with the help of which one may get closer to an explanation of this social phenomenon threatening the future of industrially developed countries. The present paper studies what effects are produced by the difference in the perception of time on the number of births and on the struggle for extending life, and, finally, how this difference influences the shape of the population pyramid and the future of the entire society. After having presented the newest research results it is worth calling attention to the fact that the consideration of time as finite has acquired a ‘dominant’ position in the majority of industrially developed countries, the expression used by T. Kuhn in his work on the change of paradigm. This worldview primarily based on rationality has had a significant role in that the number of births declined in these countries, for as D.A. Coleman put it in his keynote speech at the European Congress on Demography in 1998, ‘it is not so obvious why rational and educated people should have children’. Research results dealing with this issue show that as a result of pushing sacral considerations into the background the stability of marriages (and partnerships) decreases and the number of children also declines. For people accepting and following a finite perception of time death will be more terrible. This fear of death is a strong incentive for pushing the limits of narrowed time as far as possible. This is why the struggle for lengthening life has such an important role in scientific research, in medical practice as well as in the life of modern people. Medical science tries to meet this strong social expectation, which, besides several other factors, contributes to the growth of life expectancy at birth and, as a result, the number of births is declining. The consequences of the change of paradigm in perceiving time have modified the shape of the population pyramid: its upper part has become ‘stronger’, the lower part has been significantly ‘weakened’, and its long-term stability has been continuously weakening. And if these efforts become general, this threatens the future of the entire society.